PENGARUH LATIHAN ZIG-ZAG RUN DAN DODGING RUN TERHADAP PENINGKATAN KEMAMPUAN DRIBBLING BOLA PADA PERMAINAN FUTSAL SMAN 10 LUWU - Irwan Syam; Irsan Kahar; A. Heri Riswanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of zig-zag run and dodging run training on improving dribbling skills in futsal players at SMAN 10 Luwu. The research method used was an experimental design with a two-group pretest-posttest design. The population of this study consisted of 20 students participating in the futsal extracurricular program at SMAN 10 Luwu, all of whom were taken as the research sample using saturated sampling. The instrument employed was the Bobby Charlton Dribbling Test. Data were analyzed using descriptive statistics, normality test, homogeneity test, paired sample t-test, and independent sample t-test with SPSS 26. The results showed that: (1) zig-zag run training had a significant effect on improving dribbling skills, with t_calculated = 22.574 > t_table = 2.262 and significance value 0.000 < 0.05; (2) dodging run training also significantly improved dribbling skills, with t_calculated = 24.797 > t_table = 2.262 and significance value 0.000 < 0.05; (3) there was a significant difference between the two training methods, with zig-zag run training proving more effective in enhancing dribbling skills compared to dodging run. In conclusion, both zig- zag run and dodging run training positively affect futsal players’ dribbling skills, but zig-zag run is more effective as a training method for developing basic futsal techniques.